Clinical Audit of Physical Examinations and Cognitive Assessments for Patients on Alcohol Detoxification, in Bridge House Detoxification Unit - Sylvia Fatunla (BJPsych Open)
Aims: This audit serves to establish the practice in recent time, if patients admitted for alcohol detoxification, were examined physically and offered a cognitive assessment prior to discharge according to NICE guidelines and trust policy, as this will help to reduce missed opportunities for clients to receive effective interventions for co-morbidities.